GE_GERICHTE P/4713/2017 vom 14. November 2019 - GE Cour de justice (2019)
PREUVE ILLICITE;ABUS D'AUTORITÉ;FIXATION DE LA PEINE | CPP.141.al2; CP.179quater; LPD.1; LPD.4; LPD.12.al1; LPD.13.al1; CPP.280.letb; CPP.269.al1.leta; CPP.269.al2.leta; CP.312; CP.52; aCP.42.al1; aCP.42.al4; CP.106